2022
DOI: 10.3390/curroncol29060335
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patients’ Experiences with Telehealth before and during the COVID-19 Pandemic in British Columbia

Abstract: Background: Patients have had their cancer care either postponed or changed to telehealth visits to reduce exposure to COVID-19. However, it is unclear how these changes may have affected their experiences. We aim to identify patient characteristics that affect telehealth experiences and evaluate their preferences for using telehealth in the future. Methods: Patients who completed the Outpatient Cancer Care (OCC) Patient Experience Survey were invited to participate. They comepleted the modified OCC Survey, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Although the majority (86%) of breast and prostate cancer patients were satisfied with VFU, 16% fewer would want VFU in the future. While these findings align with trends in Canada and elsewhere, the proportion of cancer patients who reported that they would be interested in VFU beyond COVID‐19 is higher than that reported in other studies 33,41,42 . For example, of 343 breast cancer survivors receiving telephone‐VFU during the COVID‐19 pandemic in Italy, 80.3% were satisfied, but only 43.8% would want it in the future 24 .…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Although the majority (86%) of breast and prostate cancer patients were satisfied with VFU, 16% fewer would want VFU in the future. While these findings align with trends in Canada and elsewhere, the proportion of cancer patients who reported that they would be interested in VFU beyond COVID‐19 is higher than that reported in other studies 33,41,42 . For example, of 343 breast cancer survivors receiving telephone‐VFU during the COVID‐19 pandemic in Italy, 80.3% were satisfied, but only 43.8% would want it in the future 24 .…”
Section: Discussionsupporting
confidence: 69%
“…In their study of cancer patients in British Columbia, Izadi-Najafabadi et al found that lower perceived ease of use of telehealth and less education were associated with cancer patients' satisfaction with virtual care across the continuum of care. 42 Additionally, older age, female sex, non-white race, lower education, and living in an urban environment were associated with a lower likelihood of wanting telehealth after the pandemic. An earlier study by Berlin et al of patients at various phases of the cancer journey recruited from the same institution found that patient satisfaction with virtual care was associated with sex and income, but not with age or equity indexes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This is consistent with published literature reporting a general satisfaction with telemedicine [ 38 40 ] but a comparatively reduced satisfaction among older patients. Possible reasons may be that telehealth does not simulate the traditional patient experience (e.g., no physical examination) and requires them to be trained on technology, eventually compromising the clinician-patient relationship and the availability of resources and referrals for that population [ 41 43 ]. We also observed a racial discrepancy concerning the frequency of contact with health care providers, with black patients indicating lower levels of in-person contact with their physicians compared to non-black patients.…”
Section: Discussionmentioning
confidence: 99%